Suppressing Self-Discharge with Polymeric Sulfur in Li-S Batteries - Jiang, Min (Materials (Basel), 2018)
Lithium–sulfur (Li-S) batteries, due to their high theoretical capacity, intrinsic overcharge protection, and low cost, are considered as the most promising candidates for next-generation energy storage systems. To promote widespread use of Li-S batteries, various tactics have been reported to improve the columbic efficiency and to suppress the shuttle effect. Herein, we report a novel polymeric sulfur via heat radical polymerization, for the Li-S battery. The insolubles after CS(2) washing, and the changes in XRD (X-ray diffraction) results imply the formation of polymeric sulfur. Owing to the absence of cyclic S(8) molecular, the shuttle effect is depressed, and the polymeric sulfur cathodes exhibit lower self-discharge rates, higher sulfur utilization, better rates of performance, and enhanced cycling stabilities than the commercial sublimed sulfur. Thus, polymeric sulfur provides a new train of thought and tactics for restricting the formation of the dissolution of polysulfides, and self-discharge.